IoT-Based Smart Room Using Web Server-Based Esp32 Microcontroller - Ardiyallah Akbar; Zaenudin Zaenudin; Zaenul Mutaqin; Lalu Delsi Samsumar (Formosa Journal of Computer and Information Science, 2022)
The security of housing when the occupants leave for their activities is a top priority that must be met by most people, the purpose of developing a tool in this study is to utilize a Smart Room with an ESP32 microcontroller based on a Web Server as a research basis for housing security for people when they leave. by the occupants. The ESP32 microcontroller, which can be programmed via the Arduino IDE, is then used for a lamp that allows homeowners to control the lamp remotely. The mechanism of the Smart room system is that when the homeowner wants to turn on or turn off the lights, the homeowner only needs to access the Web Server so that he doesn't have to go home to turn it on.